Analisis Faktor yang Berhubungan Dengan Penerapan SMK3 Terhadap Kecelakaan Kerja Pada Pemanen Kelapa Sawit Kabupaten Batubara: Studi Literatur Riview - Al Fiza Putri Rahmadillah; Susilawati S (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Background: The process of harvesting oil palm is carried out once a week for a long period of time, with conditions of uneven soil texture and erratic weather. So work accidents can occur at any time in oil palm harvesters. Occupational accidents experienced by oil palm harvesters often occur. Both minor and serious accidents. The Occupational Health and Safety Management System (SMK3) must be applied to oil palm harvesters to minimize accidents during the harvesting process. Methods: This study uses a type of descriptive analysis with a literature review method with the aim of analyzing factors related to the application of smk3 to work accidents in oil palm harvesters. A literature search was carried out online through several websites and internet sites and 40 articles were found as search results from Neliti, Researchgate, Onesearch and Google Scholar. This research was conducted on 10 articles that met the inclusion criteria consisting of 7 national articles and 3 international articles. Articles are analyzed and processed through the stages of organize, synthesize, identify and further analyzed so as to find answers from the formulation of the problem. The results showed that the work factors (workload, work tools, personal protective equipment). Environmental factors (uneven ground conditions, and weather). Occupational and environmental factors are very significant factors in the occurrence of work accidents in oil palm harvesters. Excessive workload, work tools used and personal protective equipment worn, uneven ground conditions, namely wavy, hollow and uphill are factors of work accidents in oil palm harvesters.